Antiepileptic drug adherence among children with epilepsy attending a tertiary hospital in Rivers state, Nigeria - Gabriel-Job, Nneka; Wobo, Kininyiruchi N. (International Journal of Research in Medical Sciences, 2022)
Background: Epilepsy is a common neurologic disorder characterized by recurrent unprovoked seizures which can affect the cognitive, social and the psychological wellbeing of a child. Antiepileptic drugs (AED) adherence is necessary for good control of seizure. However, several factors can affect the adherence level among children. This present study sought to determine the factors associated with adherence to antiepileptic drugs among children with epilepsy in university of Port Harcourt Teaching Hospital (UPTH). Methods: A cross-sectional descriptive study was done among children with a diagnosis of epilepsy attending the Paediatrics Neurology Clinic of the UPTH over a 6-month period from June 2021 to December 2021. AED adherence was determined by self-report of their AED use in the month preceding the study. Descriptive statistics was used for data analysis, test for association between subgroups was carried out using Chi-square test while the difference between means was determined using the Students t-test. Results: A total of 94 children with epilepsy participated in this study. Forty-nine (52.1%) were females and 45 (47.9%) males. The mean age was 7.34 years. Thirty-eight (40.0%) had seizure control, adherence to AED was found among 39 (41.5%). Age ≤5 years (p-0.04, OR 2.4, CI 1.00-5.50), being a female (p-0.002, OR 2.8, CI 0.18-6.54), patients from upper socioeconomic class (p<0.001, OR 8.8, CI 2.27-29.5), monotherapy (p-0.007, OR 5.4, CI 1.45-19.9) and low monthly income (p-0.03, OR 0.4, CI 0.17-0.90) were factors found to significantly determine adherence to AEDs. Conclusions: AED adherence is poor among children. Making drugs affordable and available as well as adequate and continuous counselling of care givers and patients is important to ensure adherence to AED.